The vision of regional history in the Soviet textbooks of the socio-humanitarian block in 1920-1930 - Bezpalko, Bohdan; Khokhlov, Denys (Skhid, 2023)
The article examines the peculiarities of forming the vision of regional history, which was presented in the textbooks of the socio-humanitarian block of the 1920s-1930s. The historiography of the issue is analyzed. Examining the vision of regional history in Soviet textbooks, the author touched on the problem of the Soviet school system functioning in general and the history lesson in particular. The main textbooks of the specified period, which are representative of the presented issues were also analyzed, because they concern secondary general schools, that is, those children who were the basis of the school education system. The article reveals the spatial vision presented in the work of M. Yavorsky "A Brief History of Ukraine" – the main textbook of that period. Among the regions distinguished by the Soviet information policy were: Ukraine as part of the USSR; Naddniprianshchyna with the main city Kyiv, Galicia, Volyn and Zakarpattya (Transcarpathia). Also, the peculiarity of the vision of regional history, which was formed at the beginning of the next decade, is revealed. It consisted in shifting the vector from the west to the eastern spaces – Russian lands. Kyiv as a regional center receded into the background, giving way to St. Petersburg and Moscow. The specified vision deepened even more at the end of the 1930s. Textbooks of that period almost did not describe Ukrainian lands, dividing them into two artificial regions, "Eastern and Western" Ukraine. Instead, the regional vision spread to Central Asia, Kazakhstan and the Caucasus.